(untitled) (Heritage, 2023)
More than a century has passed since the third dimension of space (airspace) has become an important place where combat and non-combat activities take place. The ability of the Air Force to carry out a wide range of content of combat operations and other activities from the airspace ensured the development of new qualitative characteristics of modern armed conflicts. The absence of physical limitations, high maneuverability and dynamism, short reaction time, as well as the high intensity of actions carried out by the Air Force, have enabled these forces to have strategic importance in armed conflicts since the Second World War. In parallel with the development of civilization and the emergence of qualitatively new technologies, rapidly improved technological solutions are being developed, which are changing the way of life of people around the world, improving it literally day by day. Each technological generation brings a new level of civilizational development, leading to the symbiosis of man as a human being and modern technical and technological means. Undoubtedly, this is also the case with the development of modern weapon systems and equipment used in armed conflicts. This is also the case with the revolutionary development of new weapon systems in air forces around the world. The development of modern weapons in the air force is best seen through the development of unmanned aerial platforms (unmanned aerial vehicles). The development of these assets is a consequence of the industrial revolution of the fourth generation and the importance of these platforms in the realization of tasks in modern armed conflicts is almost immeasurable. Namely, every conflict brings exponential development of these assets, both in technical and tactical sense. The development of these means in modern armed conflicts is a continuous process that is realized on the basis of previous experiences from the tactical use of unmanned aerial vehicles in concrete combat actions. There is no doubt that the technological progress of these means is something that in the future will enable the almost unlimited use of these aircraft in the execution of a wide variety of tasks without minimal danger to human life. This paper, whose main goal is to describe the unmanned aerial vehicle as a tool for the execution of a wide range of tasks in an unlimited war format, consists of three chapters in addition to the introduction and conclusion. In the first chapter, the theoretical determination of the unmanned aerial vehicle as a weapon-equipment system was made. In the second chapter, the use of unmanned aerial vehicles is analyzed on the examples of armed conflicts in Syria and Nagorno-Karabakh. In the third chapter, an analysis of potential aviation patterns of unmanned aerial vehicles and loitering munition (also known as a suicide drone or kamikaze drone) in combat operations was carried out.